Drug Resistance Mechanisms of Acute Myeloid Leukemia Stem Cells - Niu, Jialan; Peng, Danyue; Liu, Lingbo (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a polyclonal and heterogeneous hematological malignancy. Relapse and refractory after induction chemotherapy are still challenges for curing AML. Leukemia stem cells (LSCs), accepted to originate from hematopoietic stem/precursor cells, are the main root of leukemogenesis and drug resistance. LSCs are dynamic derivations and possess various elusive resistance mechanisms. In this review, we summarized different primary resistance and remolding mechanisms of LSCs after chemotherapy, as well as the indispensable role of the bone marrow microenvironment on LSCs resistance. Through a detailed and comprehensive review of the spectacle of LSCs resistance, it can provide better strategies for future researches on eradicating LSCs and clinical treatment of AML.